2020
DOI: 10.48550/arxiv.2003.10804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting Adversarial Examples in Learning-Enabled Cyber-Physical Systems using Variational Autoencoder for Regression

Abstract: Learning-enabled components (LECs) are widely used in cyber-physical systems (CPS) since they can handle the uncertainty and variability of the environment and increase the level of autonomy. However, it has been shown that LECs such as deep neural networks (DNN) are not robust and adversarial examples can cause the model to make a false prediction. The paper considers the problem of efficiently detecting adversarial examples in LECs used for regression in CPS. The proposed approach is based on inductive conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Rosenberg et al [107] in their study of adversarial learning in cybersecurity presented CPS and industrial control systems as a case study. Cai et al [108] studied an advanced emergency braking system for self-driving cars that operates by using DNN to estimate the proximity to an obstacle. They therefore used a regression model based on variational autoencoder to detect adversarial examples in learning-enabled CPS and concluded that the proposed method can detect adversarial examples effectively with a short delay.…”
Section: Adversarial Machine Learning (Aml) and Cpsmentioning
confidence: 99%
“…Rosenberg et al [107] in their study of adversarial learning in cybersecurity presented CPS and industrial control systems as a case study. Cai et al [108] studied an advanced emergency braking system for self-driving cars that operates by using DNN to estimate the proximity to an obstacle. They therefore used a regression model based on variational autoencoder to detect adversarial examples in learning-enabled CPS and concluded that the proposed method can detect adversarial examples effectively with a short delay.…”
Section: Adversarial Machine Learning (Aml) and Cpsmentioning
confidence: 99%